Oral stories about the rescue of Jews during the Holocaust: Folklore, reality and media - E. A. Zakrvskaya (Шаги)
How are oral histories about the past “selected” into tradition? In this article the mechanisms of this selection are discussed using in-depth interviews collected in 2000–2023. The topic of the stories is the Holocaust in the occupied part of the Soviet Union and the saving of Jews by other Soviet citizens. According to our hypothesis, stories that can gain a foothold in tradition may pass through some special “filters”. They must correspond to the worldview formed by Soviet, post-Soviet and Western media and ideology (in other words they need to fit into the social framework of memory of the Holocaust). They must also have an understandable and memorable structure similar to folk fables and memorates. In addition, when remembering the Holocaust people often talk about traumatic experiences and violence, so there is a specific way to talk about these complicated topics. Stories that do not pass through these “filters” usually cannot gain a foothold in tradition — so they may be told only by eyewitnesses. On the other hand, stories that have the features described above are being told not only among eyewitnesses of events, but also among young people. They become part of family memory and of local memory.